1996
DOI: 10.1080/00207169608804514
|View full text |Cite
|
Sign up to set email alerts
|

Algebra of timed frames

Abstract: Timed frames are introduced as objects that can form a basis of a model theory fsor discrete time process algebra. An algebraic setting for timed frames is proposed and results ;oncerning its connection with discrete time process algebra are given. The presented theory oc timed frames captures the basic algebraic properties of timed transition systems for the re1a:ive time case. Further structure on timed frames is provided by adding signal inserted states and conditional transitions, thus giving a semantic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…[11]. The initial ideas about the use of a timed variant of the process algebra with propositional signals for hybrid systems were born while the second author was working on timed frames [17,43]. Similar ideas, born independently, were outlined in Ref.…”
Section: Discussion Of Main Choicesmentioning
confidence: 99%
“…[11]. The initial ideas about the use of a timed variant of the process algebra with propositional signals for hybrid systems were born while the second author was working on timed frames [17,43]. Similar ideas, born independently, were outlined in Ref.…”
Section: Discussion Of Main Choicesmentioning
confidence: 99%
“…For that purpose, we h a v e a v ailable the axioms presented in Section 2 and RSP (see Section 2.4). In [10], timed frames, which are closely related to the kind of transition systems presented by the operational semantics of, for example, BPA drt -ID and PA drt -ID, are studied in a general algebraic setting and results concerning the connection between timed frames and discrete time processes with relative timing are given. In [14], a model for BPA drt -IDlin (BPA drt -ID with nite linear recursive specications) is presented that gives an interpretation of its constants and operators on timed frames; and it is shown that the bisimulation model induced by the original structured operational semantics is isomorphic to the timed frame model.…”
Section: Discussionmentioning
confidence: 99%
“…The frames TAMC0 and TAMC1 defined here differ slightly from the ones defined in [7]. There states 46 and 47 were identified, because both were considered states of playing.…”
Section: Examplementioning
confidence: 99%
“…This section contains a survey of simple timed frame algebra and its extension with signal insertion. We refer to [7] for further details, which include results about the connection between timed frames and discrete time processes. The survey is preceded by a small example to illustrate the use of timed frames.…”
Section: Timed Framesmentioning
confidence: 99%
See 1 more Smart Citation